The Impact of Proliferation on The Poverty in The Case of North Kalimantan (Jurnal Perencanaan Pembangunan: The Indonesian Journal of Development Planning, 2026)
Indonesia's development agenda prioritizes welfare for all citizens, yet disparities persist. To address this, the government initiated a Proliferation policy of North Kalimantan Province in 2012, as a policy intervention for poverty reduction, contributing to Indonesia's SDGs implementation framework. This paper evaluates the effectiveness of proliferation in North Kalimantan province. Using a triple difference-in-differences (DDD) methodology, this quasi-experimental study compares poverty trends across North Kalimantan (treatment group) with East and West Kalimantan (control groups) during pre- and post-formation periods. This approach controls for regional characteristics and temporal shocks to ensure reliable causal inference. We aim to provide insights into the effectiveness of the expansion policy. Results show that districts in newly formed North Kalimantan experienced statistically significant poverty reduction (p